(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article addresses the problem of forming the technical preparedness of young basketball players at the initial stage of sports training, taking into account the health-oriented focus of motor activity. The purpose of the study was to scientifically substantiate and experimentally verify the effectiveness of a symmetrical training methodology for teaching basketball technical skills to children of primary school age. During the pedagogical experiment, comprehensive research methods were applied, including pedagogical observation, testing of the level of technical preparedness, and methods of mathematical statistics. The training process was based on a combination of game-based, special preparatory, and general developmental exercises with the use of simplified game situations, additional equipment, and lighter balls that corresponded to the age-related and functional capabilities of young athletes. The main principles of initial symmetrical training in basketball technical skills for primary school children involved a systematic and step-by-step approach and included the following provisions: dividing a technical element into its component parts, which enabled young athletes to better understand the structure and sequence of movements; mastering preparatory and imitation exercises before learning a specific technical skill, which contributed to the development of coordination, spatial perception, and preliminary motor readiness; learning techniques using a holistic method followed by their application in game situations, ensuring the integration of technical skills into practical play; the use of additional equipment and special markings to create a controlled environment for skill acquisition under simplified conditions; and the use of lighter and smaller balls, which facilitated the mastering of technical actions and adapted them to the physical capabilities of young basketball players. When learning technical skills in simplified conditions, primary attention was paid to the correct structure of motor actions. Traditional methodologies involve performing a significant number of preparatory exercises that ensure the gradual formation of motor skills. Basic technical skills are recommended to be mastered both through holistic learning and through step-by-step decomposition, as well as through game activities. The results of the study demonstrated a statistically significant improvement in dribbling, passing, shooting on the move, and performing combined exercises with both the dominant and non-dominant hand. The positive dynamics of technical indicators confirm the effectiveness of the proposed symmetrical training methodology and the feasibility of its implementation in the training process of young basketball players in order to improve their level of technical preparedness and ensure the health-enhancing effect of training sessions at the initial stage of preparation.